Effect of Speed of Processing Training on Older Driver Screening Measures - Eramudugolla, Ranmalee; Kiely, Kim M.; Chopra, Sidhant; Anstey, Kaarin J. (Frontiers in Aging Neuroscience, 2017)
Objective: Computerised training for cognitive enhancement is of great public interest, however, there is inconsistent evidence for the transfer of training gains to every day activity. Several large trials have focused on Speed of Processing (SOP) training with some promising findings for long-term effects on daily activity, but no immediate transfer to other cognitive tests. Here, we examine the transfer of SOP training gains to cognitive measures that are known predictors of driving safety in older adults. Methods: Fifty-three adults aged 65-87 years who were current drivers participated in a two group non-randomized design with repeated measures and a no-contact matched control group. The Intervention group completed an average of 7.9 (SD=3.0) hours of self-administered online SOP training at home. Control group was matched on age, gender and test-re-test interval. Measures included the Useful Field of View (UFOV) test, a Hazard Perception test, choice reaction time (Cars RT), Trail Making Test B, a Maze test, visual motion threshold, as well as road craft and road knowledge tests. Results: SOP training resulted in significant improvement in processing speed on the UFOV test with an average change of -45. 8ms (SE=14.5), and representing a large effect size. Performance on the Maze test also improved and was associated with the size of change in the UFOV task. Significant slowing on the Hazard Perception test was observed after SOP training. There were no effects of training on any of the other measures examined. Conclusion: SOP training effects on the UFOV task can be achieved with self-administered, online training at home, with some transfer to other cognitive tests. However, the role of search strategy on tasks requiring goal-directed rather than diffuse attention may need to be considered in future studies.